A THEORETICAL ANALYSIS OF NATURAL GAS DEHYDRATION USING MEMBRANE PROCESSES - Mellon, Nurhayati (2009)
Membrane separation processes have been known to remove saturated vapour from air stream but its use for natural gas dehydration is very limited due to the foreseen problems of methane losses and gas condensation as it moves through the membrane wall. Various mathematical models have been developed over the decades to accurately describe the membrane performance. However, the degree of complexity of these models has grown parallel with the advancement of computing power. This study aims to find the simplest model that is able to describe the membrane performance for natural gas dehydration with good degree of accuracy. It is expected that the stage cut required to meet the pipeline specification for natural gas will be small enough to make the pressure variation along membrane module negligible. Comparison on a number of published mathematical models shows that for single stage permeator, a stage cut between 4 – 6% is sufficient to bring the wet natural gas to its pipeline specification. Simulation was also performed by substituting the partial pressure with fugacity as the driving force for transport through the membrane. Results again show very little difference in membrane separation performance, which may be attributed to the very low membrane stage cut.